Ecopharma 2025 x World Pharmacists Day - Gani, Dg Siti Nur Anisah; Ismail, Farhana Fakhira; Azizi, Fatin Izyani (2025)
On November 1–2, 2025, the Faculty of Pharmacy UiTM once again stepped into the community space through EcoPharma 2025 x World Pharmacists Day, held at Sunway Wangsawalk Mall, Kuala Lumpur. Building on the success of the Safe Medication Disposal Campaign (2023) and EcoPharma@UCS (2024), this year’s initiative focused on empowering the public with knowledge on how to use, store, and dispose of medications responsibly. Carrying the theme “Community Empowerment through Safe Medication Use and Pharmaceutical Waste Disposal,” the program united academic, community, and industry forces. Over 20 booths, activities, and health screenings were set up, led by passionate scientists and academia, pharmacy students and supported by a strong line-up of partners. This impactful program was made possible through the support of the Industry Matching Programme (IMaP) grant from the Ministry of Higher Education (MOHE), successfully secured by Dr. Hisyam Abdul Hamid. Strategic collaboration played a key role, with strong backing from the Pharmacy Practice & Development Division (MOH), Pharmaceutical Association of Malaysia (PhAMA), and Alpro Pharmacy Sdn. Bhd. Their presence not only added credibility but also widened the program’s outreach through shared expertise and logistical support. Other notable partners included Pfizer (M) Sdn. Bhd., Duopharma (M) Sdn. Bhd., NGOs, and community partners - Seksyen 4, Wangsa Maju Residents’ Association, added further strength to the message by engaging in educational booths, health engagement sessions and Home Medication Review (HMR).